Analisa Dan Perancangan Sistem Informasi Reservasi Kamar Hotel Menggunakan Model View Controller (MVC) Pada Aplikasi Web - Fahmi Awaludin; Winda Liana Sari; Gathan Alfaridzi Hidayat; Muhammad Rizky Darmawan; Aries Saifudin (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
In the current era of globalization, with increasingly advanced developments, the internet is a necessity for everyone in carrying out activities. Reservation or borooking a hotel room is an activity where a customer comes to the hotel to order a room and stay in the room that has been booked. Orders are made by customers, at Hotel Royal Ambarrukmo Yogyakarta, the ordering process and data collection of customers who will stay are still done manually. So that customers have to come to the hotel to place an order directly. This hotel room booking information system is an application that can help speed up registration or registration at the reception. Cancellations can also be managed directly by the admin or receptionist. Thus providing another convenience in placing an order. In addition, the hotel room booking system at the Hotel Royal Ambarrukmo Yogyakarta also experienced problems in terms of managing hotel capacity which was limited during the COVID-19 pandemic. This can cause confusion and dissatisfaction for guests who have made reservations but did not get the desired room. Therefore, it is necessary to analyze and design a better system using the Model-View-Controller (MVC) in order to overcome the above problems. In this model, an inventory management system and room cleanliness are needed that are integrated with the booking system to ensure the availability of safe and comfortable rooms for guests. In addition, a pricing system is also needed that can adjust room rates according to demand and room availability.